SOSIALISASI PERAN AKUNTANSI, PAJAK DAN INVESTASI MODAL DALAM MENDUKUNG KEBERLANJUTAN BISNIS DI ERA DIGITAL PADA SISWA SMK IPTEK TANGERANG SELATAN - Fitriyah; Fithrah Kamaliyah; Sri Agustini (Jurnal Abdi Citra, 2026)
Research and Community Service (PKM) is one of the manifestations of the Tri Dharma of Higher Education. The purpose of the PKM activity is to foster lecturers in improving their abilities, skills, and independence as well as the existence of Pamulang University as an agent of change in order to provide significant benefits to the community. This time the Unpam Accounting Study Program held PKM at SMK IPTEK South Tangerang. The purpose of the PKM activity is to provide socialization of the role of accounting, capital investment tax in supporting business sustainability in the digital era and to increase financial knowledge and skills in managing finances which are very important to be applied in everyday life as provisions in the future. The implementation of PKM in the form of material presentations, discussions and training at the end of the session to determine the extent to which the material can be absorbed is done by questions and answers to students at SMK IPTEK.